Simulation Model of GPRS Channels Operation as a Part of the Railway Traffic Coordination System - Akhmetov, Bakhytzhan; Lakhno, Valeriy; Yerkeldessova, Gulzada; Sarzhanov, Taizhan; Issaikin, Dmitriy (International Journal of Electronics and Telecommunications, 2019)
The paper analyzes the prospects for the formation and implementation of digital data transmission technologies on railways of Kazakhstan, taking into account the potential for the development of high-speed railway transport (HSRWT), as well as new approaches for solving the development problems of advanced automated dispatch control systems (ADCS). It was shown that the solution of these problems is possible by automatization of the train traffic coordination based on the use of the potential of the GPRS data transmission technology. The work further developed models and algorithms used in ADCS of the railway transport. There has been carried out the formalization of the tasks of navigation data transmission for ADCS and for the subsystems of the railway rolling stock movement coordination, including HSRWT using GPRS data transmission technology. Also, the article describes a modernized algorithm for simulation of the GPRS channels operation in ADCS. The proposed algorithm differs from the existing ones by the ability to make predictive estimates for determination of the railway rolling stock location. Also, the developed algorithm provides opportunities for coordination of the trains movement, taking into account the optimization of the GPRS resources use.